Quality of databases about infectious diseases notified in Vila Velha city, Espírito Santo state, Brazil, from 2007 to 2017 (Brazilian Journal of Health Research, 2021)
Introduction: Databases are important assessment and planning tools, to help identifying priority targets for health interventions and their respective impacts. Objective: Evaluating the quality of databases about exanthematic diseases, leprosy, viral hepatitis and meningitis in Vila Velha City, ES, Brazil, based on analyzing completeness and consistency levels. Methods: Descriptive study conducted with data available at the Notifiable Disease Information System (Sinan) from 2007 to 2017. Results: Low completeness levels were observed in 52% of exanthematic disease variables; 37.5%, in hepatitis; and 25%, in meningitis. On the other hand, leprosy presented excellent completeness levels at all analyzed variables. Consistency among variables associated with all four disease groups reached 91.31%, on average – it ranged from 73% to 100%. Conclusion: It is necessary implementing measures to improve the quality of infectious disease reports in Vila Velha City.
Keywords: Information Systems; Epidemiological Monitoring; Exanthema; Human Viral Hepatitis; Leprosy; Meningitis